2020
DOI: 10.3390/socsci9120224
|View full text |Cite
|
Sign up to set email alerts
|

Relation between College Students’ Conservatism and Negative Stereotypes about Social Groups

Abstract: This study examined the interrelations among political attitudes and negative stereotypes in U.S. undergraduates. Participants answered questions measuring conservatism, social dominance orientation, Global Belief in a Just World, and religiosity. This research employed two measures of stereotypes: modern sexism and feelings about 15 social groups. It was hypothesized that conservatives would show more evidence of negative stereotypes than liberals would. The study revealed that indeed conservatives show stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Insofar as right‐wing beliefs and stereotypes toward marginalized outgroups are related (e.g., Beyer, 2020; Sparkman & Eidelman, 2016) then acceptance of these stereotypes is overdetermined: it could be predicted from NCC, right‐wing beliefs, or both. One potential solution is to assess NCC, stereotype acceptance, and right‐wing beliefs as a part of a meditational model (e.g., De Cristofaro et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Insofar as right‐wing beliefs and stereotypes toward marginalized outgroups are related (e.g., Beyer, 2020; Sparkman & Eidelman, 2016) then acceptance of these stereotypes is overdetermined: it could be predicted from NCC, right‐wing beliefs, or both. One potential solution is to assess NCC, stereotype acceptance, and right‐wing beliefs as a part of a meditational model (e.g., De Cristofaro et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a diversity of views about the extent to which China and the Chinese people should shoulder the blame for the COVID-19 pandemic, democrats and republicans express increasingly negative views of Asian people and China specifically (Griffin, Sides, and Tesler 2020). Thus, although explicitly prejudiced views generally (Beyer 2020;Sidanius et al 1996) and anti-Asian views in particular (Griffin et al 2020) may be more pronounced among white conservatives, we expect that racial bias among white liberals will also lead them to act in ways that disadvantage Asian Americans relative to white Americans when primed to think about a threat from Asia.…”
Section: Political Ideologymentioning
confidence: 90%
“…Although studies show that individuals with less education are more likely to score high on measures of traditional prejudice (Wellman 1993;Wodtke 2012), middleand upper-class whites often oppose race equality policies and practices when such policies are believed to harm their own communities or take advantages away from their families (Lewis and Diamond 2015;Wellman 1993). And although many studies suggest a positive association between conservatism and racial prejudice (Beyer 2020;Sears and Henry 2003;Sidanius, Pratto, and Bobo 1996) or between conservatism and an ingroup bias favoring white Americans (Eastwick et al 2009;Hoyt and Goldin 2015), studies also find evidence of racial bias among white liberals (Byrd et al 2015;Daniels at al. 2021;Dupree and Fiske 2019).…”
Section: Political Ideologymentioning
confidence: 99%
“…Another explanation could be that our sample generally reported to be quite liberal in terms of its political orientation, even though the mean age suggests that our sample did not mainly comprise students (for which such a trend could be expected). This may likely have counteracted pronounced differences in state empathy between in-group and out-group because people with a liberal political ideology have recently been found to hold fewer negative stereotypes toward ethnic out-groups [e.g., 55 . Furthermore, it has been shown that liberals tend to be more motivated to show empathy towards both members of the in-group and of out-groups 44 .…”
Section: Discussionmentioning
confidence: 99%